2014
DOI: 10.1016/j.bjp.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing properties and mucilage content of Pereskia aculeata from different substrates

Abstract: Physiologic growth parametersWound healing A B S T R A C TPereskia aculeata Mill., Cactaceae, is a cactus with high mucilage production, well-known for its nutritional properties. Folk use consists on skin injuries, and mucilage is probably involved in the wound healing activity. This work studied some aspects of its cultivation, specifically regarding soil (substrate), to correlate the effects of nutritional content to mucilage production and to the wound-healing property. Plants were grown under five differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
0
15
0
4
Order By: Relevance
“…However, there are only few studies about P. aculeata leaves phytochemicals and their therapeutic potential (Pinto et al, 2012;Pinto and Scio, 2014). Recently, Carvalho et al (2014) reported the in vitro wound healing activity of the mucilage extracted from the leaves of this species, and Pinto et al (2015) showed that the hydromethanolic fraction from the crude extract of the leaves presented central and peripheral antinociceptive activity in mice.…”
Section: Introductionmentioning
confidence: 94%
“…However, there are only few studies about P. aculeata leaves phytochemicals and their therapeutic potential (Pinto et al, 2012;Pinto and Scio, 2014). Recently, Carvalho et al (2014) reported the in vitro wound healing activity of the mucilage extracted from the leaves of this species, and Pinto et al (2015) showed that the hydromethanolic fraction from the crude extract of the leaves presented central and peripheral antinociceptive activity in mice.…”
Section: Introductionmentioning
confidence: 94%
“…In vitro tests confirm emollient action in the relief of inflammation besides helping to heal burns (Sartor et al, 2010). P. aculeata extracts promote wound healing activity by increasing the closing velocity, blood flow and deposition of tissue collagen, corroborating its traditional use as an anti-inflammatory and in wound healing (Pinto et al, 2016), mainly due to the proliferative action of the tissue fibroblasts (Carvalho et al, 2014), the increase in the collagen deposition and the greater speed of the contraction of the edges of the wounds (Pinto et al, 2016).…”
Section: Pereskia Aculeata Mill Cactaceaementioning
confidence: 63%
“…Recent studies have addressed the cytotoxic activity of Pereskia aculeata ethyl acetate extracts against different human cell lines (Carvalho et al, 2014;Nurestri et al, 2009).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Wound healing activity has been attributed to the mucilage of cactus leaves (Thornfeldt, 2005;Aburjai and Natsheh, 2003). However, this property has never been tested under experimental conditions (Carvalho et al, 2014). Wound healing is a complex process involving steps of cellular migration and proliferation, especially, but not only, of fibroblast cells (Krishnan, 2006).…”
Section: Pharmaceutical Usesmentioning
confidence: 99%